The Concept of Al-SyÄá¹ibÄ«â€™s al-Taâ€˜Äruá¸ wa al-TarjÄ«á¸¥: Scientific Faith and Methodology Solution to Legal IstinbÄá¹ - Farkhani, Farkhani; Elviandri, Elviandri; Nugroho, Sigit Sapto (Fakultas Syariah IAIN Purwokerto, 2018)
Al-Taâ€˜Äruá¸ wa al-tarjÄ«á¸¥ is a methodology offered by al-SyÄá¹ibÄ« to overcome problems that often arise in fiqh issues faced by the people. This study is a descriptive literature study (library research) aims to determine how the concept of al-Taâ€˜Äruá¸ wa al-tarjÄ«á¸¥ offered, with fahm al-naá¹£á¹£ methods that exist in its al-MuwÄfaqÄt. To al-SyÄá¹ibÄ«, no at-taâ€˜Äruá¸ (contradiction) in texts but there is a contradiction among mujtahids (Muslim jurists) in understanding the texts. Then, the mujtahids (jurists) should not be in a hurry to do istinbÄá¹ al-á¸¥ukm (taking out the law) which originated from the áº“Ähir contradictory arguments. A depth and universal study toward contradictive postulates seems needed by mujtahid both using their precision and intelligence. Because of the precision and intelligence mujtahids are varying, it causes the appearance of a conflict between mujtahids in looking at the arguments. To find a solution to the problem, the offer is the use of tarjÄ«á¸¥ method, looking for the most powerful arguments, and then serving them as the basis to take a single istinbÄá¹ al-á¸¥ukm.